The Power of Exclusion in Agrarian Conflict of Bangko-Bangko National Natural Park, West Lombok - Anugrah, Galang (UI Scholars Hub, 2020)
Land exclusion (prevention and restriction of access) plays an important role in triggering agrarian conflicts in Indonesia. Previous studies tended to see the state and private companies as the main actors driving the exclusion process, while the reasons behind it were merely caused by the capital. However, the process of exclusion is also led by forestry and nature conservation. This paper aims to explore the case of agrarian conflicts that occur in the Bangko-Bangko National Natural Park, by examining the power of exclusion as a conceptual framework (Hall et al. 2011). By using qualitative research methods, the data were collected through observation techniques, in-depth interviews, and documentation studies. This study reveals that the exclusionary processes are primarily driven by 3 types of power: regulation, force, and legitimation. Regulation is carried out by the state, synergistically with the legitimation of conservation (by the notion of the common good) and the use of repressive means, to secure claim over Bangko-Bangko and prevent local people’ access to the area. The local community has found themselves were tried to exclude from the land they claimed as their own—by using the legitimation of indigenous people—and have resisted this claim from the state.